The protective effects of cabozantinib against high glucose-induced damages in in vitro renal glomerular endothelial cells model via inhibition of early growth response-1 (Egr-1). Issue 4 (1st April 2022) - Ye, Hanlu; Yan, Jingjing; Wang, Qiong; Tian, Hui; Zhou, Lei
ABSTRACT: Cabozantinib is a tyrosine kinase inhibitor with anti-tumor activity in kidney cancer. However, the efficacy of cabozantinib in other renal diseases has never been reported. Here, we focused on exploring the effect of cabozantinib on diabetic nephropathy (DN). The biofunctions of cabozantinib in human renal glomerular endothelial cells (hGECs) under high glucose conditions have been investigated. We found that cabozantinib ameliorated high glucose-induced oxidative stress in hGECs with decreased production of mitochondrial reactive oxygen species (ROS) and increased glutathione peroxidase (GSH-PX) activity. Cabozantinib ameliorated high glucose-induced reduction in the expression of endothelial nitric oxide synthase (eNOS) and the production of nitric oxide (NO) in hGECs. It also suppressed the expression of pro-inflammatory mediators, interleukin-6 (IL-6) and monocyte chemokine protein 1 (MCP-1), against high glucose exposure in hGECs. Cabozantinib reduced the expression of early growth response-1 (Egr-1) in high glucose-treated hGECs, while Egr-1 overexpression abolished the protective effects of cabozantinib against high glucose in hGECs. In conclusion, cabozantinib protected hGECs from high glucose-induced oxidative stress, NO deficiency, and inflammation via regulating Egr-1. These findings suggest that cabozantinib might be used as an adjuvant to control DN. Graphical abstract: uf0001